Sosialization of Sea Turtle Under Threatened in Pasir Jambak - Febrinal Febrinal; Azzahrah Khairunnisa Mardhiyah; Maysyarah Ardiana; Zultsatunni’mah Zultsatunni’mah; Pati Hariyose; FITRA ARYA DWI NUGRAHA (Fakultas MIPA Universitas Negeri Padang, 2019)
All sea turtles are listed as endangered and critically endangered by IUCN Red List due to human consumption and lifestyle. In West Sumatra, Pasir Jambak Beach is an important habitat for nesting of sea turtles, but human activities in this area becomes serious threats for sea turtles. Based on our interview, the local people of Pasir Jambak still consume the sea turtle eggs and mistaken for the effect of this egg to human. During our activity, we share our knowledge especially to the children of Pasir Jambak, hoping that they will not continue the habit of consuming the sea turtle egg, and become more concerned to the conservation of sea turtle around them. All of us were responsible for the rapid decline of sea turtle populations. We also take an action for cleaning the Pasir Jambak beach from the plastic trash and released the Tukik (juvenile) to help increasing the sea turtle population in nature.